Improving the prediction of the Atmospheric neutrino flux using the atmospheric muon flux - Honda Morihiro (EPJ Web of Conferences, 2019)
It is well known that the correlation of atmospheric neutrinos and muons are simply correlated in the energy region of 1–10 GeV, and used for the test bench of the hadronic interaction model used for the calculation of the atmospheric neutrino flux. However, the correlation becomes unclear for neutrinos in the energy range below 1 GeV, which is important for the study of mass ordering of neutrino and CP phase of the neutrino mass. We extend the study of the correlation to the lower neutrino energies and find that the atmospheric muon flux observed at high altitude shows a good correlation to the atmospheric neutrino flux, and could be used to calibrate the hadronic interaction model.